The Politics of Sponsorship and Sports Justice: The Role of Corporate Influence in Shaping Indonesian Sports (Indonesian Sports Justice Review, 2025)
Corporate sponsorship plays a significant role in the commercialization of Indonesian sports, yet it raises critical questions about sports justice, equity, and the welfare of athletes. This paper explores how corporate sponsorship and commercial interests shape the landscape of Indonesian sports, analyzing the ethical implications for athlete well-being and fairness. It addresses concerns such as the prioritization of profit over athlete health, the exclusion of certain sports or athletes due to sponsorship bias, and the implications for competition fairness. Through a case study of key sponsorship deals in Indonesian sports, the paper evaluates the role of corporate influence in shaping the priorities of sports organizations, and it proposes strategies for ensuring that sponsorship agreements promote justice, accessibility, and fairness for all athletes.